Karate agility: The new competition category for children`s physical development with very high test/re-test reliability - Styriak, R.; Billman, M.; Augustovicova, D. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2020)
Background and Study Aim. Early specialisation does not guarantee later competitive success. Development of general motor skills appears to be the key factor in achieving maximum success in sports at an older age. To prevent burn-out and early specialisation, the Slovak Karate Union introduced a new competition discipline - the Karate Agility Course (KAC), where young karateka apply their fundamental motor skills. The aim of this research was to examine the reliability of the KAC as a new competition discipline for young karate athletes. Material and Methods. Forty four young national level karateka participated in the study: 28 males (age 9.1±1.8 y, body mass 40.0±12.4 kg) and 16 females (age 9.9±2.7 y, body mass 38.9±8.8 kg). All performed the KAC for both age categories twice: test and re-test sessions were carried out on separate occasions, 1 week apart. Results. Test and re-test results showed the KAC to be reliable. Net time and total time for 8-11 year old children did not display any difference between the test and the re-test. The SEM and ICC for both variables were <5% and >.90, respectively. The Bland and Altman analyses reported a mean difference (bias) ± the 95% limits of agreement. Conclusions. The study showed that the new KAC discipline, with effort patterns replicating karate combat demands, can be considered as a reliable, karate-specific field test for assessing karatekas` physical performance.